Renaissance man - Vajna, Andrew; Marshall, Penny; De Vito, Danny; Hines, Gregory; Burstein, Jim. ([United States] Cinergi Pictures Entertainment, 1994)
Danny DeVito plays an advertising man who was fired from his job. He signs up for unemployment and takes a job teaching thinking skills to Army recruits. He teaches the class by making them read and critically analyze Hamlet.
VHS.
Executive producer: Buzz Feitshans ; producers: Sara Colleton, Robert Greenhut, Elliot Abbot ; director of photography: Adam Greenberg ; music: Hans Zimmer.
Danny de Vito, Gregory Hines.
Keywords: Comedy